The Use of Logistic Performance Measures in the Sugar and Alcohol Sector: An Exploratory Case Study - Barbosa, Danilo Hisano; Herrera, Vânia Érica; Kurumoto, Juliana Sayuri; Musetti, Marcel Andreotti (Revista Gestão da Produção Operações e Sistemas, 2007)
This paper presents part of a broader study performed by a research group in logistics, which evaluated the status of an entire Supply chain, regarding the excellence of its logistic practices, using some excellence models as a conceptual background. Thus, the research problem consisted in finding out which logistic performance measures for the group of cost metrics; asset management; customer service and productivity are used by a xx sugarcane plant. In order to answer that question, it was used the descriptive-exploratory research and the research strategy based on a case study, comparing the variables selected to investigation and the plant reality. The research results showed that the plant is focused on costs and productivity metrics, with less attention to customer service and asset management. Furthermore, it was verified regarding the evaluation perspective a greater attention to a Benchmarking perspective, with less attention to the functional view and hardly any activities connected to the Supply chain perspective. Keywords: Logistics, Performance Measurement, Performance Measures, Sugarcane.